Reliability-Oriented Method of Flexible Pavement Management - Uglova Evgenia; Tiraturyan Artem; Aslanyan Grigory (MATEC Web of Conferences, 2018)
The article dwells on the reliability-oriented method of flexible pavement management. The research revealed the limitation of the existing method in the field of highway condition assessment. The proposed approach was applied using the data obtained during the field tests from the operated sections of the M-4 DON Highway. Within the framework of the study the assessment criteria scale for the condition of flexible pavement designs was developed. The integral indicator of the road safety and the pre-failure condition coefficient was calculated with the subsequent designation of repair measures at the sites. Also, the analysis of the results was carried out on the basis of which a pavement strength failure rate curve was plotted. The results of the study were compared with the results obtained in foreign studies on fatigue fracture research.